1970
DOI: 10.3329/jard.v7i1.4429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Containers, Chemicals and Indigenous Materials on Incidence of Wheat Pests in Storage

Abstract: (3.92-28.98), red flour beetle (7.58-43.08) and rice weevil (0.75-9.08) was found in naphthalene. Camphor had the similar population level of those three insect pests during the study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…It makes the field workers and researchers clear to train the people or farmers in the respective manner, that is, for control measures effectiveness reaches almost a year, the method to store such amount of grains to escape from pest attack. Use of metal bins for storage of stocked and useful for prevention of the pest attack Ali et al (2009) reported that tin containers and plastic bags proved to be best in storing the wheat grains as compared to the gunny bags and earthen pots. Baloch et al (1994) reported that jute bags are the reason of high infestation of insects in the grains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It makes the field workers and researchers clear to train the people or farmers in the respective manner, that is, for control measures effectiveness reaches almost a year, the method to store such amount of grains to escape from pest attack. Use of metal bins for storage of stocked and useful for prevention of the pest attack Ali et al (2009) reported that tin containers and plastic bags proved to be best in storing the wheat grains as compared to the gunny bags and earthen pots. Baloch et al (1994) reported that jute bags are the reason of high infestation of insects in the grains.…”
Section: Discussionmentioning
confidence: 99%
“…The reason of high infestation in jute or gunny bags is that these storage facilities support ventilation and also increase the moisture content of the grains which results in moulding, webbing and insect infestation. In contrast, the plastic bins and metal containers do not allow any air to flow in and also maintain the moisture content, thus keep the insect infestation low (Ali et al, 2009). The interviews revealed that more than 85% of the people can identify the stored grain pests.…”
Section: Discussionmentioning
confidence: 99%
“…The wheat grains are stored in tin kouta, earthen potor motka, metal and plastic containers, gunny and polythene bags. These types of storage materials are cheap and easy to handle (Ali et al 2009). Sometimes various type of indigenous materials e.g.…”
Section: Use Of Containersmentioning
confidence: 99%
“…It was found that camphor and naphthalene are cheap and very effective against stored grain pests (Latif et al 2004). Ali et al (2009) tested the effectiveness of various containers (Tin kouta, earthen pot, plastic container and gunny bag), chemicals (Naphthalene and camphor) and indigenous materials (neem leaf powder and sand) against Angoumois grain moth, red flour beetle and rice weevil in stored wheat. A significant lowest population of grain moth (1.40-7.93), red flour beetle (6.40-35.33) and rice weevil (0.20-9.13) was found in plastic containers.…”
Section: Use Of Containersmentioning
confidence: 99%
See 1 more Smart Citation